Rostral Anterior Cingulate Cortex–Ventrolateral Periaqueductal Gray Circuit Underlies Electroacupuncture to Alleviate Hyperalgesia but Not Anxiety-Like Behaviors in Mice With Spared Nerve Injury - Zhu, Xixiao; Xu, Yingling; Shen, Zui; Zhang, Haiyan; Xiao, Siqi; Zhu, Yichen; Wu, Mengwei; Chen, Yeqing; Wu, Zemin; Xu, Yunyun; He, Xiaofen; Liu, Boyu; et al. (Frontiers in Neuroscience, 2022)
Neuropathic pain is a common cause of chronic pain and often accompanied by negative emotions, making it complex and difficult to treat. However, the neural circuit mechanisms underlying these symptoms remain unclear. Here, we present a novel pathway with comorbid chronic pain and anxiety. Using chemogenetic methods, we found that activation of glutamatergic projections from the rostral anterior cingulate cortex (rACCGlu) to the ventrolateral periaqueductal gray (vlPAG) induced both hyperalgesia and anxiety-like behaviors in sham mice. Inhibition of the rACCGlu -vlPAG circuit reduced anxiety-like behaviors and hyperalgesia in spared nerve injury (SNI) mice. Moreover, electroacupuncture (EA) could effectively alleviate hyperalgesia and anxiety-like behaviors in SNI mice, and the related mechanisms were investigated. We found that chemogenetic activation of the rACCGlu-vlPAG circuit effectively blocked the analgesic effect of EA in SNI mice but did not affect the anxiolytic effect of EA. In conclusion, we demonstrated a novel circuit mechanism in which the rACCGlu-vlPAG circuit plays an important role in SNI-induced hyperalgesia and anxiety-like behaviors. And this neural circuit is involved in the analgesic but not anxiolytic effects of EA.